A study on the mechanism of school support to improve school adjustment of rural left-behind children——Analysis based on CEPS (2013–2014) data - Shunxu Peng; Zhenyu Li; Jiapeng Ai; Jia Liu; Jingjing Shi; Hao Liu (PLoS ONE, 2025)
School adjustment is related to the educational achievements and future career development of rural left-behind children. School support is an important institutional measure to promote the school adjustment of rural left-behind children in China. Using Structural Equation Modeling (SEM) based on CEPS data, this paper analyzed the effects of school support on rural left-behind children’s school adjustment, and found that: (1) school support effectively improves rural left-behind children’s school adjustment ability; (2) school support enhances students’ school adjustment ability by improving their educational expectation and mental health, especially the effects of teachers’ relationship support and school soft environment support are significant; (3) teacher support has a greater effect on students’ school adjustment ability than environment support, and soft environment support enhances students’ school adjustment ability by improving their mental health, while the impact of hard environment support is weaker. This study provides theoretical support for the formulation of intervention policies for rural left-behind children and offers practical evidence for understanding the relationship between school education and family education.